Pilot scale degradation study of 16 selected volatile organic compounds by hydroxyl and sulfate radical based advanced oxidation processes. (20th January 2019) - Fernandes, André; Makoś, Patrycja; Khan, Javed Ali; Boczkaj, Grzegorz
Abstract: The studies of effective technologies for complete degradation of the volatile organic compounds (VOCs), are very important due to the high biotoxicity of the VOCs which makes the biological technologies ineffective. It also increases the risk of VOCs emission instead of their treatment when using open air biological technologies. In the present study, different types of Advanced Oxidation Processes (AOPs) were investigated for the degradation of several VOCs in a model pilot scale effluent, simulating effluents from bitumen production. The goal of this paper is to reach effective VOCs and wastewater degradation to make the bitumen production a cleaner process. O3, H2 O2, O3 /H2 O2 (the so called peroxone), persulfate (PS) and peroxymonosulfate (PMS) were processes chosen for this work. Heat activation enhanced the total VOCs degradation in PS and PMS technologies, which achieved higher effectiveness than H2 O2 . Peroxone process at 40 °C achieved the highest efficiency of all processes studied needing only 60 min to completely degrade all compounds without any oxidation by-products. Sulfur containing VOCs (VSCs) were completely degraded in a shorter treatment time and nitrogen containing VOCs (VNCs) needed more time of treatment in all technologies studied. The preference of the hydroxyl and sulfate radicals for degradation of oxygen containing VOCs (OVOCs) had different behavior depending on the group of compounds and should be considered in future research for combined radical processes. Highlights: Temperature increased the removal efficiency of VOCs by PS and PMS processes. Volatile nitrogen-containing organic compounds were more persistent to degradation. Peroxone achieved complete degradation of VOCs in 60 min. No toxic by-products of the studied VOCs were detected. Effective VOCs degradation allows cleaner production.